Electrochemistry and electrophoresis of mercury cysteine and ditizone complexes - Martin, Lynwill Garth (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Chemistry and Polymer Science))--Stellenbosch University, 2008.